Flesh browning in Fuji, Cripps pink and SCS427 Elenise apples - Carlesso, Cristiane (2022)
This study aimed to evaluate the flesh browning index of SCS427 Elenise, Fuji and Cripps Pink apples after cutting, simulating the preparation of minimally processed food. Two distinct experiments were performed, one using newly harvested fruits and the other after storage of 75 and 120 days at a common cold atmosphere at 1ºC. The fruits were cut in the equatorial portion and the flesh was evaluated by digital colorimetric sensors throughout 0 to 48 hours after cutting. ‘Cripps Pink’ apples presented the highest flesh browning in both experiments. Whereas ‘SCS427 Elenise’ apples showed the lowest flesh browning and took longer to reach their maximum index than the other cultivars, which means they are more recommended for minimally processed food than ‘Fuji’ and ‘Cripps Pink’ apples.